ERROR ANALYSIS IN ESL WRITING - Yasmine Liong Pui Kwan Abdullah (Universitas Muhammadiyah Semarang, 2021)
English is a globally recognised language spoken almost all over the world. When learning the English language, one needs to acquire four skills. They need to develop listening, speaking, reading and writing skill. Writing is difficult for English as Second Language (ESL) learners to acquire. It is an essential skill as they need it for many purposes in their daily lives. However, Malaysian pupils, being ESL learners and for some foreign language learners, it is even more challenging to master the skill. Teachers need to identify the area of weaknesses faced by their pupils so that they can choose appropriate materials and practical pedagogical approaches to help them learn. Error analysis is an effective way to help teachers obtain information on their pupils' kind of errors. This study aims to identify grammatical errors made by 77 Year Five primary pupils from a suburban school, focussing only on tenses. The analysis is done based on a short essay written by the pupils. This study suggests that by understanding their pupils' weaknesses, teachers will be able to develop interventions for the betterment of their pupils' learning.